A radical public administration? Green radicalism and policy influence among local environmental officials in Sweden. Issue 3 (3rd May 2016) - Hysing, Erik; Olsson, Jan; Dahl, Viktor
ABSTRACT: Green radicalism among local environmental officials in Sweden is examined with the aims of theoretically elaborating on different dimensions of Green radicalism in the context of public administration, exploring the dimensionality of Green radicalism among officials, and examining the extent to which Green radicalism is associated with policy influence. Three types of Green radicalism are identified: Green ethics, Green institutional change, and Green activism. Survey data ( N  = 701) show that the three theoretical dimensions are present among officials, and that there is no negative association between radicalism and influence. It is primarily officials with Green activism beliefs who perceive themselves as able to influence policy. These findings suggest a need for more nuanced understanding of and further studies into the role of public administration in the quest for more radical Green reforms.